Influence of ultrasonic agitation on the abrasive wear characteristics of Al-Cu/ 2 vol% Grp composite. (11th January 2022) - Gupta, Ramendra Kumar; Vashishtha, Nitesh; Sapate, S G; Udhayabanu, V; Peshwe, D R
Abstract: In the present study, the abrasive wear behavior of Al–4.4 wt% Cu composite reinforced with 2 vol% graphite particle (Grp ) has been investigated. In the preparation of composite, Ultrasonic Treatment (UT) is provided in the composite melt for the uniform distribution of reinforcement particles. Two bond abrasive wear tests are conducted for composites treated with ultrasound and without UT and base alloy. The results of abrasive wear studies indicate that at 5 and 10 Newton (N) loads, the composite with UT has a higher coefficient of friction (COF) and wear resistance than that of the base alloy (Al–4.4 wt% Cu). Whereas, at 15 and 20 N load, the value of COF and wear resistance is lower for the composite. Two abrasive wear mechanisms micro-plowing and micro-cutting have been observed during the wear tests of base alloy and composites. The analysis of worn-out sample surfaces at higher load reveals that softened material layer due to localized elevation in temperature between two contact surfaces during wearing acts as a tribolayer in base alloy while in composites both softened material layer and graphite layer have worked together as tribolayer.